Respuesta :

Answer: y = -3(x + [tex]\frac{5}{6}[/tex])² + [tex]\frac{37}{12}[/tex], [tex](-\frac{5}{6}[/tex], [tex]\frac{37}{12})[/tex]

Step-by-step explanation:

First, you need to complete the square:

y   = -3x² - 5x + 1

-1                    -1  

y - 1 = -3x² - 5x

y - 1 = -3(x² + [tex]\frac{5}{3}x[/tex]

y - 1 + -3([tex]\frac{25}{36}[/tex]) = -3(x² + [tex]\frac{5}{3}x[/tex] + [tex]\frac{25}{36}[/tex])

           ↑                     ↓            ↑

                                  [tex]\frac{5}{3*2}[/tex] = [tex](\frac{5}{3*2})^{2}[/tex]

y - 1 - [tex]\frac{25}{12}[/tex] = -3(x + [tex]\frac{5}{6}[/tex])²

y - [tex]\frac{12}{12}[/tex] - [tex]\frac{25}{12}[/tex] = -3(x + [tex]\frac{5}{6}[/tex])²

y  - [tex]\frac{37}{12}[/tex] = -3(x + [tex]\frac{5}{6}[/tex])²

y = -3(x + [tex]\frac{5}{6}[/tex])² + [tex]\frac{37}{12}[/tex]

Now, it is in the form of y = a(x - h)² + k   where (h, k) is the vertex

Vertex = [tex](-\frac{5}{6}[/tex], [tex]\frac{37}{12})[/tex]